The Internal Migration and Social Sustainability in the Agro-Export Sector of the Ica Valley, 2025 - Silva Rojas, David Antonio (2026)
This study examined the relationship between internal migration and social sustainability in the agro-export sector of the Ica Valley, Peru, during 2025. Using a qualitative and interpretative approach, it explored the experiences of migrant workers—how they arrive, adapt, and perceive their working and living conditions, as well as their own well-being. Twenty interviews with migrants and five with key informants were conducted, complemented by a review of official documents and recent regulations. Findings show that migration is primarily driven by economic needs and family responsibilities, but it also represents an opportunity for social advancement. Most migrants integrate quickly into operational roles, though their inclusion is limited by temporary employment and insufficient social protection. Despite income improvements, challenges persist in housing, health, and transportation. Therefore, achieving social sustainability requires strengthening corporate responsibility and public policies aimed at inclusion. Overall, the Ica agro-export model depends on balancing migrants’ adaptive strategies, corporate social commitment, and regional public management.